Incidence of gastrointestinal cancers by ethnic group in England, 2001-2007. - Ali, R; Barnes, I; Cairns, B; Finlayson, A; Bhala, N; Mallath, M; Beral, V (2013)
To compare the incidence of six gastrointestinal cancers (colorectal, oesophageal, gastric, liver, gallbladder and pancreatic) among the six main 'non-White' ethnic groups in England (Indian, Pakistani, Bangladeshi, Black African, Black Caribbean and Chinese) to each other and to Whites. We analysed all 378 511 gastrointestinal cancer registrations from 2001-2007 in England. Ethnicity was obtained by linkage to the Hospital Episodes Statistics database and we used mid-year population estimates from 2001-2007. Incidence rate ratios adjusted for age, sex and income were calculated, comparing the six ethnic groups (and combined 'South Asian' and 'Black' groups) to Whites and to each other. There were significant differences in the incidence of all six cancers between the ethnic groups (all p<0.001). In general, the 'non-White' groups had a lower incidence of colorectal, oesophageal and pancreatic cancer compared to Whites and a higher incidence of liver and gallbladder cancer. Gastric cancer incidence was lower in South Asians but higher in Blacks and Chinese. There was strong evidence of differences in risk between Indians, Pakistanis and Bangladeshis for cancer of the oesophagus, stomach, liver and gallbladder (all p<0.001) and between Black Africans and Black Caribbeans for liver and gallbladder cancer (both p<0.001). The risk of gastrointestinal cancers varies greatly by individual ethnic group, including within those groups that have traditionally been grouped together (South Asians and Blacks). Many of these differences are not readily explained by known risk factors and suggest that important, potentially modifiable causes of these cancers are still to be discovered.